Answer:
x= 4
Y= -1
Z= 3
step by step procedure:
let x+y+z=6, x-y+z=8, x+y-z=0 be equations 1, 2, and 3 respectively.
- subtract equation 2 from equation 1 ; x+y+z-(x-y+z) = 6 - 8
- y+y = -2 , 2y = -2, therefore y = -1
- substituting the value of y into equations 1, 2, and 3 . we get x+z=7---eqn 4, x+z=7---eqn 5 and x-z=1---eqn 6
- now add equation 6 to equation 5 ; x+z+(x-z)=7+1 ,x+x=7+1, 2x=8, therefore x=4
- put the value of x (x=4) back into equation 5; 4+z=7, z=7-4, therefore z=3.
you are welcome bro....